Eye-gaze Strategies During Facial Emotion Recognition in Neurodegenerative Diseases and Links With Neuropsychiatric Disorders. Issue 1 (3rd March 2022) - Polet, Kévin; Hesse, Solange; Morisot, Adeline; Kullmann, Benoît; Louchart de la Chapelle, Sandrine; Pesce, Alain; Iakimova, Galina
Abstract : Background: Facial emotion recognition (FER) is primarily and severely impaired in individuals with the behavioral variant of frontotemporal dementia (bvFTD) and is often mildy impaired in individuals with Alzheimer disease (AD) or Parkinson disease (PD). Such impairment is associated with inappropriate social behaviors. Objective: To determine whether FER impairment is linked to the use of inappropriate eye-gaze strategies to decode facial emotions, leading to misinterpretation of others' intentions and then to behavioral disorders. Method: We assessed FER in 9 individuals with bvFTD, 23 with AD, and 20 with PD, as well as 22 healthy controls (HC), using the Reading the Mind in the Eyes (RME) Test and the Ekman Faces Test. Eye movements (number and duration of fixations) were recorded with an eye-tracking device. Behavior was assessed using the Neuropsychiatric Inventory. Results: FER was mildly impaired in the AD and PD groups and severely impaired in the bvFTD group. FER impairment was accompanied by an increase in the number of fixations and a more attracted gaze toward the lower part of one's face. FER impairment and an increase in the number of fixations were positively correlated with behavioral disorders. Conclusion: Our study demonstrated a link between FER impairment, modification of eye-gaze strategies during the observation of emotional faces, and behavioral disorders in individuals with bvFTD and those with AD or PD. These results suggest that an eye-gaze strategy rehabilitation program could have beneficial effects on emotion recognition and behavioral disorders in individuals with these diseases.